Adsorption of Metolachlor and Its Transformation Products, ESA and OXA, on Activated Carbons - Alicia Gomis-Berenguer; Pauline Sidoli; Benoît Cagnon (Applied Sciences, 2021)
Three activated carbons from lignocellulosic residues and a commercial carbon have been tested for the removal of the herbicide metolachlor and its two degradation transformation products, named ESA and OXA, in aqueous solutions. The kinetics and equilibrium adsorption were studied for the four materials, showing higher adsorption capacities for the three molecules on the carbon materials chemically activated by potassium carbonate, mainly associated with its greater porous development, especially in the range of microporosity. Additionally, the chemical composition of the adsorbents also highlighted their important influence on the ESA and OXA adsorption process. The efficient adsorption of both compounds—even at low initial concentrations—allows a removal efficiency of up to 80% to be reached, revealing promising perspectives for the use of biomass-derived carbon materials for the elimination of not only the herbicide metolachlor, but also its degradation compounds from contaminated wastewater.